Ślady biblijnej, świętej Północy i antycznej Hyperborei w literaturze patrystycznej i średniowiecznej - Kochanek, Piotr (Vox Patrum, 2022)
„Hyperborea” is a concept well known to researchers of antiquity. Also, the sacred biblical North, as the antithesis of Gog’s sinister North, is well known to Bible scholars. This article takes these two concepts as a starting point. However, the purpose of this article is to confront the biblical and ancient vision of the North with selected patristic and medieval sources. It is about presenting changes in the historical and geographical understanding of the term „Hyperborea”. Greek literature describes Hyperborea as a paradise located in the farthest reaches of the North. This vision of the North seems to be similar to a northern paradise in the Bible. However, the patristic literature, which is well acquainted with the Greek myth of the Hyperboreans, does not apply it to any exegetical analyzes. Hyperborea is for the Fathers of the Church an „extension” of Scythia, so it is neither a paradise nor an ideal promised land. It is part of the ecumene and has all the good and bad features of the territory that ordinary people inhabit. Hyperborea has been transformed from a Greek ideal land into a historical, existing reality. The name was therefore applied both to the Scythian territory and to the areas north of Scythia. However, the development of the geographical horizon constantly shifted the concept of „Hyperborea” further north. The line of this geographical horizon was marked in Byzantine literature by Theophanes in the eighth century and by Nicephorus Gregoras in the fourteenth century. The latter pointed to Moscow Ruthenia as the Christian Hyperborea in the north-east. The same line of geographical horizon in Latin literature was very delicately indicated by Adam of Bremen in the eleventh century, who wrote about Hyperborean Scandinavia. Next to the geographical horizon, there was a strictly literary horizon, dominated by the classical topos, based on texts written by Greek and Latin classical authors.